2022
DOI: 10.3390/jcm11030739
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Leukocytoclastic Vasculitis, Treatment, and Outcome in Patients with Ulcerative Colitis: A Systematic Review of the Literature

Abstract: Leukocytoclastic vasculitis (LCV) is a rare extraintestinal manifestation (EIM) of ulcerative colitis (UC). Observations about its association with UC stem from case reports and small case series. Due to its rarity, more rigorous cross-sectional studies are scarce and difficult to conduct. The aim of this systematic review was to synthetize the knowledge on this association by reviewing published literature in the form of both case reports and case series; and report the findings according to the Preferred Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Detailed descriptions of the clinicopathological features of ulcerative colitis have been recently published [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. A gene that was highlighted in this research was CD274 ( PD-L1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of the clinicopathological features of ulcerative colitis have been recently published [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. A gene that was highlighted in this research was CD274 ( PD-L1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, aseptic nasal septal abscess has also been reported as a rare manifestation of PG in patients with UC (Yilmaz et al 2011;Chang 2018;Tomioka et al 2018;Yu et al 2020) (Table 1). Additionally, leukocytoclastic vasculitis (a form of small-vessel vasculitis) is one of the extra-intestinal manifestations of UC, and it has been reported that 41% of patients with UC complicated with leukocytoclastic vasculitis are positive for ANCA (Pantic et al 2022). Therefore, patients with PR3-ANCA-positive UC are prone to develop small-vessel vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous works have found that systemic causes account for the majority of LCV cases [ 2 , 18 ] However, in a relatively large case series of 93 patients, idiopathic cases accounted for 44.1%. And extracutaneous involvement was not discovered in 60.2% of cases [ 18 ]. Extracutaneous involvement, despite extensive workup, was negative in our patient.…”
Section: Discussionmentioning
confidence: 99%